2012
DOI: 10.2215/cjn.00850112
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis-Induced Regional Left Ventricular Systolic Dysfunction

Abstract: Summary Background and objectives The hemodialysis procedure may acutely induce regional left ventricular systolic dysfunction. This study evaluated the prevalence, time course, and associated patient- and dialysis-related factors of this entity and its association with outcome. Design, setting, participants, & measurements Hemodialysis patients (105) on a three times per week dialysis schedule were studied between March of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 27 publications
7
91
0
11
Order By: Relevance
“…Regional assessment of myocardial contractility in tandem with perfusion allowed us to study the development of myocardial stunning more precisely, demonstrating co-existing reductions in contractile function and perfusion and only partial recovery postdialysis. The pattern of injury, and peak of the effect, was in keeping with echocardiography-based studies performed by our group and others [6,23]. We observed myocardial stunning as early as 70min from the start of treatment, consistent with early changes in myocardial perfusion described in PET studies [9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regional assessment of myocardial contractility in tandem with perfusion allowed us to study the development of myocardial stunning more precisely, demonstrating co-existing reductions in contractile function and perfusion and only partial recovery postdialysis. The pattern of injury, and peak of the effect, was in keeping with echocardiography-based studies performed by our group and others [6,23]. We observed myocardial stunning as early as 70min from the start of treatment, consistent with early changes in myocardial perfusion described in PET studies [9].…”
Section: Discussionsupporting
confidence: 90%
“…However, using data from previous echocardiography-based studies and assuming a mean±SD of 4.81.3 new regional wall motion abnormalities (RWMAs) per patient with standard dialysis [33] [33], 11 patients per group would be required to have a 90% chance of detecting a decrease in new RWMAs from 4.8 in standard dialysis to 3.0 in the HDF group, significant at the 5% level. Such a reduction would be clinically significant and in keeping with other dialysis based interventions shown previously to reduce dialysisinduced myocardial stunning [23,33]. to HD or HDF for two weeks, after which they attended a cardiac MRI scan which was performed before, during, and after a dialysis session.…”
Section: Cardiac Imagingsupporting
confidence: 67%
“…HD itself causes recurrent and cumulative ischemic injury to the heart, brain, and other organs (2). Recurrent HD-induced myocardial stunning results in long-term contractile dysfunction, abnormal ventricular morphology, and increased mortality (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…However, some previous studies showed a lower incidence of HD-induced reduction of EF. 15,16 It can be explained by the absence of diabetes and pre-existing cardiac disease in their study population. A second explanation might be the difference in the method used for the evaluation of regional LV systolic dysfunction.…”
Section: -14mentioning
confidence: 94%
“…Because one study showed that reduction of EF was different during different time of HD and mostly occurred during early phase of HD. 15 However, some studies showed that repeated HD may improve LV dysfunction over time. 26,27 As our study was only two-session study, our study did not support this finding.…”
Section: -14mentioning
confidence: 99%